Relationship between alcohol expectancies and attitudes towards rape victims - Tan, Jun Yi (Nanyang Technological University, 2020)
Alcohol use has been consistently associated with perceptions of alcohol-related sexual assault. However, little research has been conducted regarding individuals’ sex-related alcohol expectancies, which refer to beliefs about the effects of alcohol on sex-related behaviours. This study aimed to examine the role of participants’ alcohol use and sex-related alcohol expectancies on their perceptions of alcohol-related sexual assault, taking into account the effects of priming victim alcohol or non-alcohol consumption. The Alcohol Use Disorders Identification Test— Consumption (AUDIT-C) was administered to assess participant alcohol use, while the Drinking Expectancy Sexual Vulnerabilities Questionnaire (DESV-Q) was used to assess participants’ beliefs about the effects of alcohol on women. One hundred and sixty-six young adults aged 18- 36 (M = 22.0, SD = 3.15) were randomly assigned to read one of two vignettes that depicted a rape scenario, where the victim had drunk either an alcoholic or non-alcoholic drink prior to the assault. A measure assessing attributions of blame and responsibility to the hypothetical victim was used alongside the Attitudes toward Rape Victims Scale (ARVS), which assessed participants’ perceptions of rape victims in general. Results showed that participants with strong beliefs about the sex-related effects of alcohol had significantly more negative attitudes towards rape victims in general (OR = 1.07), and attributed more blame (η2 = .03) and responsibility (η2 = .07) to the victim when reading about a specific victim who had consumed alcohol prior to the assault. Implications of these results and future directions are discussed.